2018
DOI: 10.1158/1535-7163.mct-17-0792
|View full text |Cite
|
Sign up to set email alerts
|

Induced Telomere Damage to Treat Telomerase Expressing Therapy-Resistant Pediatric Brain Tumors

Abstract: Brain tumors remain the leading cause of cancer-related deaths in children and often are associated with long-term sequelae among survivors of current therapies. Hence, there is an urgent need to identify actionable targets and to develop more effective therapies. Telomerase and telomeres play important roles in cancer, representing attractive therapeutic targets to treat children with poor-prognosis brain tumors such as diffuse intrinsic pontine glioma (DIPG), high-grade glioma (HGG), and high-risk medullobla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
(40 reference statements)
5
40
0
1
Order By: Relevance
“…S1, B and C ). Our previous studies also showed that human normal fibroblasts, colonic epithelial cells, skin keratinocytes, skin melanocytes, and skin fibroblasts are not as sensitive to 6-thio-dG as telomerase-positive cancer cells and 6-thio-dG causes G2/M arrest in telomerase-positive cells with negligible effect in telomerase-negative cells [14] , [22] , [23] . These results are consistent with the proposed mechanism of action of 6-thio-dG indicating that expression of telomerase in cells increases the sensitivity to 6-thio-dG with minimal effect on normal cells.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…S1, B and C ). Our previous studies also showed that human normal fibroblasts, colonic epithelial cells, skin keratinocytes, skin melanocytes, and skin fibroblasts are not as sensitive to 6-thio-dG as telomerase-positive cancer cells and 6-thio-dG causes G2/M arrest in telomerase-positive cells with negligible effect in telomerase-negative cells [14] , [22] , [23] . These results are consistent with the proposed mechanism of action of 6-thio-dG indicating that expression of telomerase in cells increases the sensitivity to 6-thio-dG with minimal effect on normal cells.…”
Section: Resultsmentioning
confidence: 75%
“…We also showed that targeting telomerase with 6-thio-dG overcame therapy resistance in pediatric brain tumors (demonstrating that 6-thio-dG can cross the blood brain barrier) [24] . In addition, we demonstrated sensitivity to 6-thio-dG in BRAF and checkpoint inhibitor–resistant melanomas [22] , [23] . Here in this study, we extended our preclinical studies to more clinically relevant lung cancer model systems.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, it is hopeful that 6‐thio‐dG will work as a front line or salvage therapy towards targeting therapy‐resistant cancer cells and may sensitize tumors that are refractory to checkpoint inhibitors providing long‐term durable responses. In a preclinical study on therapy‐resistant pediatric brain tumors, it was also demonstrated that 6‐thio‐dG can cross the blood brain barrier thus expanding the utility of this new approach …”
Section: Telomerasementioning
confidence: 99%
“…In a preclinical study on therapy-resistant pediatric brain tumors, it was also demonstrated that 6-thio-dG can cross the blood brain barrier thus expanding the utility of this new approach. 45…”
Section: Htert Inhibitionmentioning
confidence: 99%